Penerapan Media Wordwall untuk Meningkatkan Hasil Belajar IPAS Materi Gaya pada Siswa Kelas IV SD - Cecilia Kabrina Sitepu; Yosita Theresia Tarigan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Learning IPAS (Science and Social Studies) on the topic of force in fourth-grade elementary school still faces challenges due to students’ low learning outcomes, as the learning process tends to be teacher-centered and lacks the use of interactive learning media. This condition causes students to be less active, less motivated, and experience difficulties in understanding the concept of force. This study aims to improve students’ learning outcomes in IPAS on the topic of force through the implementation of Wordwall media in fourth-grade elementary school students. The research employed a Classroom Action Research (CAR) method conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. The subjects of this study were fourth-grade elementary school students. Data were collected through learning activity observations, learning outcome tests, and documentation. The results showed that the implementation of Wordwall media improved students’ activeness, motivation, and engagement during the learning process. Furthermore, students’ learning outcomes increased, as indicated by the growth in the number of students achieving learning mastery in each cycle. Wordwall media also created a more interesting, interactive, and enjoyable learning environment that helped students understand the concept of force better. The implication of this study indicates that Wordwall media can be used as an effective digital learning medium to improve the quality of learning processes and IPAS learning outcomes on the topic of force in fourth-grade elementary school.